2017
DOI: 10.3892/mmr.2017.8234
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic signature predicts the distant relapse in patients with ER+ breast cancer treated with tamoxifen for five years

Abstract: Tamoxifen is the most commonly used drug to treat estrogen receptor positive (ER+) breast cancer. However, many patients with ER+ breast cancer have experienced resistance and other adverse side effects following treatment with tamoxifen. Furthermore, clinical and pathological parameters have thus far failed to predict the efficiency of tamoxifen administration. Therefore, gene signature based models for the prediction of survival time of such patients are urgently needed. In the current study, gene expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…Among the top DEGs, up-regulated expression of genes such as COL10A1 , MMP1 , MMP11 , and BUB1 ; down-regulated expression of genes such as ADH1B , CIDEC , FABP4 , AQP7 , RBP4 , CDO1 , FIGF , and LPL were reported to be differentially expressed in breast and or other cancers by various authors using microarray profiling in western population 26–38 , showing concordance with the present study. In the present study, we found up-regulation of cell cycle genes such as BUB1 , CCNA2 , CCNB2 , and CDC2 ; up-regulated expression of BUB1 , CCNA2 , CCNB2 and CDC2 has also been reported in breast 39,40 and several other cancers 41–46 using microarray and were found to be associated with poor prognosis of the disease 44,4749 . Overexpression of the above cell cycle genes may be contributing to the uncontrolled proliferation of the tumour cells and hence may serve as biomarkers and targets for therapy.…”
Section: Discussionsupporting
confidence: 75%
“…Among the top DEGs, up-regulated expression of genes such as COL10A1 , MMP1 , MMP11 , and BUB1 ; down-regulated expression of genes such as ADH1B , CIDEC , FABP4 , AQP7 , RBP4 , CDO1 , FIGF , and LPL were reported to be differentially expressed in breast and or other cancers by various authors using microarray profiling in western population 26–38 , showing concordance with the present study. In the present study, we found up-regulation of cell cycle genes such as BUB1 , CCNA2 , CCNB2 , and CDC2 ; up-regulated expression of BUB1 , CCNA2 , CCNB2 and CDC2 has also been reported in breast 39,40 and several other cancers 41–46 using microarray and were found to be associated with poor prognosis of the disease 44,4749 . Overexpression of the above cell cycle genes may be contributing to the uncontrolled proliferation of the tumour cells and hence may serve as biomarkers and targets for therapy.…”
Section: Discussionsupporting
confidence: 75%
“…The protein binds to and activates cyclin-dependent kinase 2, thereby facilitating the G 1 /S and G 2 /M transitions. 39 CCNA2 is also a prognostic biomarker for ER-positive breast cancer, 40 and overexpression of CCNA2 in tumor tissue predicts poor survival in patients with pancreatic ductal adenocarcinoma. 41 …”
Section: Discussionmentioning
confidence: 99%
“…The protein binds to and activates cyclin-dependent kinase 2, thereby facilitating the G 1 /S and G 2 /M transitions. 39 CCNA2 is also a prognostic biomarker for ER-positive breast cancer, 40 and overexpression of CCNA2 in tumor tissue predicts poor survival in patients with pancreatic ductal adenocarcinoma. 41 DNA topoisomerase II alpha, encoded by the TOP2A gene, modulates DNA topology during transcription by catalyzing the breakage and recombination of double-stranded and is also involved in DNA transcription and replication, chromatid separation, and chromosome condensation.…”
Section: Discussionmentioning
confidence: 99%
“…29 , 30 It was reported that ER-positive patients who have high expression of CCNA2 or CCNB2 have inferior survival. 31 , 32 KIF4A, KIF20A and KIF23 are all mitotic kinesins and have a highly conserved motor domain involving ATP-binding and microtubule-binding sequences. 33 They all promote the proliferation of breast cancers, and treatment with tamoxifen reduced the expression of these three proteins.…”
Section: Discussionmentioning
confidence: 99%